Redox gene expression of adipose-Derived stem cells in response to soft hydrogel - Fahsai Kantawong (2018)
© TÜBİTAK. Adipose-derived stem cells (ADSCs) showed morphological change to a neuron-like shape, and presented neuronal lineage bias when cultured on a very soft surface. To gain basic insight into gene expression relating to neuronal lineage bias in ADSCs, we examined the correlation between the gene expression levels of neuronal markers and redox proteins that were considered to have a close relation with lineage specification in stem cells. ADSCs were cultured on gelatinous soft hydrogel for 1-2 weeks. The time course changes in the expressions of neuronal genes (TUBB3 and NSE) and redox genes (TRX1, SOD1, SOD2, PRX2, GSTT1, and GSTP1) were monitored using real-time PCR. It was found that the TUBB3 gene had significantly upregulated compared to the control condition for tissue culture polystyrene, indicating that the neuronal gene expression of ADSCs could be achieved on soft hydrogel without the addition of any supplement. The expressions of the TRX1 and SOD1 genes were also observed to have significantly upregulated on the soft hydrogels. The results demonstrate that the upregulation of the neural marker of TUBB3 in the ADSCs correlates well with the upregulation of the redox genes of TRX1 and SOD1, when cultured on appropriate soft hydrogel substrates.